Gender Influence on Students’ Learning Preferences: An Assessment of the Learning Styles of Postgraduate Students at African International University - NGALA, FRANCISCA WAVINYA (Advances in Social Sciences Research Journal, 2018)
This paper is a write up of a study that sought to examine the relationship between gender and learning preferences of post-graduate students at Africa International University (AIU) in Nairobi, Kenya. The study employed a descriptive survey design which used crosssectional approach to data collection. The population of the study consisted of all the 397 post-graduate students at Africa International University at the time of data collection. The sample size used was made up of 199 participants from the post-graduate Diploma, Masters’ level and Doctoral programmes. A questionnaire guide was the instrument used to collect information from the participants on their gender demographics and their preferences. Statistical Package for Social Sciences (SPSS) was used to analyse the data. A modified version of the Grasha - Riechmann Student Learning Style Scales (GRSLSS) was the learning style inventory that was used to measure the learning preferences. The findings revealed that gender was not significantly related to the ways Post-graduate students at Africa International University preferred to learn.